Применение онтологий в области информационных технологий для обеспечения рынка труда - Волошина, Н. А.; Касумов, Т. А. (ХНУРЭ, 2008)
The given work is devoted a question of employment of graduates of high schools in sphere of information technologies. As a way of the decision of this problem the ontology which will contain knowledge from a subject domain of employers and high schools is offered. The system models an abstract image of the employee on the basis of company requirements, and a concrete image of the graduate proceeding from knowledge which are received by the student. And the further comparison of these two images on presence of the general qualities.
Keywords: рынок труда